Diseño y prototipado de un aerogenerador de flujo turbulento orientado a un suministro energético. - Sinchiguano Molina, Germánico (2017)
The design and prototyping of a turbulent flow wind turbine was developed in order to build a source of sustainable energetic supply for production in remote areas based principally on the analysis of uptake of wind origin by vertical axis (Windspire), through a selection of NACA aerodynamic profiles like: NACA 0015, NACA 0018 and NACA 0021, giving construction priority to these profiles due to a good capture of the potential and selecting the profile NACA 0015, to present the greater area of contact with the wind. This analysis was determined under a simulation carried out in the SolidWorks program (flow simulation), where the critical points of the assembled wind turbine were highlighted, when it operates under load, getting as a result, a safe behavior by the wind pickup to give it speed (1 m / s and 5 m / s) and power to the wind turbine, regardless of the turbulence of the wind flow. It is finally important to point out that the most common speed values during the time period are between 3.5 m / s and 4.0 m / s, being the reference point in considerations of means of production and design stability.